The Role of Digital Platforms in Da’wah and Counseling: Between Opportunities and Challenges - R, Naurah Jasmine Zakia; Rahmania, Rizky Dwi (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
In general, counseling and guidance play an important role in helping clients achieve positive behavioral changes. To ensure the effectiveness of counseling and guidance programs, a systematic evaluation of their implementation is required, including supervision, assessment, and monitoring of outcomes. However, in practice, many counseling and guidance programs still lack adequate evaluation mechanisms and do not fully adhere to proper standards. The purpose of this study is to describe how counseling and guidance program evaluations are implemented, while also providing recommendations, analysis, and factors to consider when deciding whether to continue or terminate a program. The term “program evaluation” has been widely used in the field of education in this context, highlighting the importance of improving the quality of counseling implementation. The findings further emphasize that evaluations should involve feedback from those being assessed as well as relevant stakeholders. Moreover, evaluation in counseling and guidance programs includes both process evaluation and outcome evaluation.